PENERAPAN KODE ETIK PROFESI AUDITOR DALAM MENJAGA KUALITAS AUDIT: (Studi Kasus Kantor Akuntan Publik XX) - Nilam Cahyanti; Rintan Nuzul Ainy (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2024)
This research was motivated by the desire to photograph the practice of implementing a code of ethics in terms of maintaining audit quality by auditors, especially in today's digital era. The writing of this article aims to provide an overview of the practice of implementing the code of ethics regarding maintaining audit quality by auditors. The results of this research are expected to be used as reference material to see the practical side of the application of the code of ethics. For academics, this paper is useful to see the real practice of implementing the auditor's code of ethics. This research is a qualitative research conducted using observational data collection techniques, interviews and documentation. Based on the results of data analysis and information obtained, it is concluded that the auditor's professional code of ethics in maintaining audit quality is very important, the better the code of ethics applied by the auditor, the better the quality of audit results. An auditor must also apply the principle of objectivity that affects the quality of the audit produced. Finally, professional behavior upadate knowledge by attending seminars or workshops about the latest knowledge, the better the quality of audit results because auditors can provide opinions according to existing percentages